Diagonal and off-diagonal types of disorder in condensed matter theory - Rudavskii, Yu.; Ponedilok, G.; Petriv, Yu. (Condensed Matter Physics, 2000)
In the paper we investigate the distribution function of a diagonal type of disorder, their relation with microscopic model parameters and structural correlation functions. The conditions are obtained for which the distribution of random values of atomic energy levels will be of Gauss type. The numerical analysis of dispersion D is performed. The distribution to the hydrogen-like atom chemisorption on an amorphous system is applied.